Clinical observation of a patient with realization of atopic march - N. A. Ilenkova; N. L. Prokopceva; O. S. Konopleva; L. V. Stepanova (Лечащий Врач, 2021)
Atopic dermatitis (AD) makes its debut in early childhood and is considered as the first step of the «atopic march», being a significant risk factor for the formation of other atopic diseases: allergic rhinitis and bronchial asthma. Complex therapy of AD should include not only anti-inflammatory drugs, but also means which restore the barrier function of the skin (emollient). Without adequate skin care, the disease becomes severe and contributes to the involvement of new target organs in the inflammatory process.